EXPLORING INTERSECTIONS OF NURSING HOME CULTURE, IMPROVEMENT, AND DOCUMENTATION-RELATED ATTITUDES. (20th December 2022) - Baker, Hannah
Abstract: Documentation of patient care and characteristics is an important part of nursing home (NH) operations, affecting financial aspects, quality improvement (QI) efforts, inter-provider communication, and potential for medical errors. However, relationships among NH culture, QI, and documentation-related attitudes are unclear. This study explored Wisconsin NH staff and administrator perspectives on these variables (n = 10 in 8 NHs), using interviews structured on a composite of Schein's organizational culture typology and Shortell's Quality Improvement Implementation Survey concepts. Interview questions related to perspectives and emotions about NHs' documentation quality, OC, QI efforts, and nursing staff turnover. Verbatim transcription, member checks, and team-based transcript coding and analysis ensured good data quality. Thematic analysis was used to construct a "storyline" and refine the original theoretical model. Sample data fit the model well, supporting the perception of pairwise relationships between NH OC, QI, and documentation. One of Schein's culture types was not represented in the sample. Attitudes and perceived influences on documentation-related quality were mostly negative. This research contributes to knowledge on long-term care and could point future research toward (1) similar work in dissimilar NHs to replicate results, (2) closer examination of staffing variability, (3) quantitative work on effects of education and auditing on documentation-related attitudes, and (4) strategies to improve attitudes without increasing staff stress levels.